Growth patterns of Nothofagus pumilio trees along altitudinal gradients in Tierra del Fuego, Argentina - Massaccesi, Guillermina (2008)
The influence of ecological factors resulting from altitude on growth characteristics of Nothofagus pumilio was analyzed. N. pumilio forests grow in the southern Andes from near sea level to 600 m.a.s.l. Eight study sites were selected in the southwestern area of Tierra del Fuego, on north- and south-facing slopes, and distributed along an altitudinal gradient (200–600 m.a.s.l.). Growth cycles throughout time were identified. The correlation between climate and tree growth was determined. Tree diameter and height decreased whereas stand density increased towards tree-line. South-facing slopes showed higher values in common growth variability, probably because of stronger climatic controlling factors. Climate-growth correlation models revealed long-term temperature influences on growth variability, and showed variations among the different plots. Differences were detected in the spectral power component of the chronologies throughout the altitudinal profile. The series had a significant spectral peak at frequencies around 7 years, possibly related to mast seeding cycles. This signal became weaker as the altitude increased probably due to lower seed production. These results suggest a strong altitudinal component in growth variability of N. pumilio in Tierra del Fuego.